2018
DOI: 10.1002/jum.14668
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Shear Wave Elastography in Patients With Autoimmune Liver Disease

Abstract: Shear wave elastography is a novel noninvasive adjunct to liver biopsy in evaluation and staging of patients with ALD, showing the potential for serial evaluations of disease progression and treatment responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…130,137 The AUROCs for 2D-SWE in diagnosing ≥F2, ≥F3, and F4 were 0.85, 0.85, and 0.86, respectively. 138 Other studies reported similar AUROCs ranging from 0.781 to 0.84, 139,140 showing higher predictive efficacy compared to APRI and FIB-4 (AUROC, 0.84 vs. 0.57 vs. 0.63). 140 A single-center study in South Korea on point SWE which generates shear wave in one area revealed an AUROC of 0.8, similar to the results of studies from other countries that showed point SWE outperforming APRI and FIB-4.…”
Section: Imaging Modalitiesmentioning
confidence: 88%
“…130,137 The AUROCs for 2D-SWE in diagnosing ≥F2, ≥F3, and F4 were 0.85, 0.85, and 0.86, respectively. 138 Other studies reported similar AUROCs ranging from 0.781 to 0.84, 139,140 showing higher predictive efficacy compared to APRI and FIB-4 (AUROC, 0.84 vs. 0.57 vs. 0.63). 140 A single-center study in South Korea on point SWE which generates shear wave in one area revealed an AUROC of 0.8, similar to the results of studies from other countries that showed point SWE outperforming APRI and FIB-4.…”
Section: Imaging Modalitiesmentioning
confidence: 88%
“…[ 9 , 14 ] The use of elastic techniques in AIH is also increasing, and in this study, we also found a positive correlation between LS measurements and liver fibrosis grades in previous studies, which is consistent with many other studies. [ 12 , 15 ] Maciej used ultrasound elastography (transient elastography, TE and two-dimensional shear wave elasticity) to measure liver and spleen stiffness to predict the incidence of AIH cirrhosis. When the cutoff value of liver and spleen stiffness was set at 16.1 kPa and 29.8 kPa, respectively, the AUC could reach 0.93 to 0.95.…”
Section: Discussionmentioning
confidence: 99%
“…There are two recent studies of autoimmune liver disease[ 59 , 60 ]. Because of the low prevalence of this disease, these studies included patients with autoimmune hepatitis, primary biliary cholangitis, primary sclerosing cholangitis, and overlap syndrome, all of which have different liver damage patterns[ 59 , 60 ]. For this reason, the AUROCs of autoimmune liver disease according to fibrosis stage were lower than those of chronic viral hepatitis[ 59 , 60 ].…”
Section: Role Of 2d-swe In Assessing Liver Fibrosismentioning
confidence: 99%